Effectiveness of Schema Therapy on Components of Love and Emotional Empathy in Single Women with Fear of Marriage - Behiroz , Azar; Khayatan, Felor; Yousefi , Zahra (Psychology of Woman Journal, 2025)
Objective: This study aimed to examine the effectiveness of schema therapy on the components of love and emotional empathy in single women with a fear of marriage.Materials and Methods: The research method was semi-experimental with a pretest-posttest and follow-up design with a control group. The statistical population included all female students at Payame Noor and Azad universities in Semirom in 2023. Participants were selected based on inclusion and exclusion criteria. A total of 30 individuals were chosen through convenience sampling and randomly assigned to experimental and control groups (15 individuals in each group). A pretest was administered to both groups. The experimental group received schema therapy over 8 sessions, while the control group did not receive any intervention. Data were collected using the Sternberg Love Components Questionnaire (1996), the Baron-Cohen and Wheelwright Emotional Empathy Questionnaire (2004), and the Delkhamoosh Fear of Marriage Questionnaire (2007). The data were analyzed using repeated measures analysis of variance (ANOVA) in SPSS version 23.Findings: The results showed that schema therapy significantly increased the components of love and emotional empathy in single women with a fear of marriage. The therapeutic effects were maintained during the follow-up phase (F = 9.95, P < 0.01).Conclusion: Based on the findings of this study, schema therapy can be utilized to enhance the components of love and emotional empathy in single women with a fear of marriage.